PENGARUH PENAMBAHAN CAMPURAN ASAM AMINO ESENSIAL DAN KOLIN (AMINOVIT) DALAM PAKAN TRADISIONAL TERHADAP PENAMPILAN BABI BALI JANTAN - I K., SUMADI; ASTAWA, I P. ARI; WIBAWA, A. A. P. P.; PUGER, A. W. (Majalah Ilmiah Peternakan, 2018)
This study was conducted to know the right amount of amino acid and choline (Aminovit) mixture in traditional feeds on male bali pigs for 12 weeks. The design used was a completely randomized design (CRD) with four treatments and each treatment consisted of 4 replications, so 16 male bali pigs using with a weight range of 11.60- 14.10 kg. The feed treatment were P0 treatment: mixed base feed of 49.5% yellow maize and 49.5% pollard; P1: treatment P0 + 0,50% Aminovit; P2: P0 + 1.00% Aminovit; and P3: treatment P0 + 1.5 Aminovit. The performance measured were initial body weight, final body weight, body weight gain, feed intake, and feed conversion ratio (FCR). The results showed that increasing Aminovite in the feed increased of final body weight, body weight gain and feed consumption, and feed efficiency.